The catastrophic worrier : why you worry & how to stop - Davey, Graham (New Harbinger Publications, Inc., 2023)
"Excessive and distressing worrying is a problem that affects everyone at some point in their lives, but for some people this can become a lifelong affliction. Catastrophic worry can turn even imagined setbacks into a cascade of devastating events, leading to loss of sleep, lower self-confidence, poor decision making, and even health problems. In this guide, leading worry expert Graham Davey explains why we worry, and offers readers a clear path to stopping catastrophic worry so they can regain control and live a happier life"--